SISTEM INFORMASI INVENTORY BERBASIS WEB PADA CV. ESTIKA ADVERTISING: CV Estika Advertising;Inventory;Laravel;PHP;HTML;and MySQL. - Adriana, Windy; Pariyadi; Prammudya, M Alif (JURNAL AKADEMIKA, 2022)
The development of technology today has helped humans in doing their work so that it becomes easier, faster and satisfying results. One of those technologies is the computer. Because by using a computer, office work can be completed properly, quickly, and the results are very satisfying. CV. Estika Advertising which is engaged in printing, the information system that runs is still manual in recording data. The information system to be built uses the HTML and PHP programming languages, and uses the MySQL database, XAMPP, and the Laravel framework. The system produced from this research is a web-based Inventory Information System at CV. Estika Advertising. Reports that will be generated from this system are in the form of stock reports, incoming goods reports, and outgoing goods reports. With this system, it is hoped that it can help make it easier for CV. Estika Advertising in recording and processing goods data.